2013
DOI: 10.3389/fpsyg.2013.00185
|View full text |Cite
|
Sign up to set email alerts
|

Visual attention to dynamic faces and objects is linked to face processing skills: a combined study of children with autism and controls

Abstract: Although the extant literature on face recognition skills in Autism Spectrum Disorder (ASD) shows clear impairments compared to typically developing controls (TDC) at the group level, the distribution of scores within ASD is broad. In the present research, we take a dimensional approach and explore how differences in social attention during an eye tracking experiment correlate with face recognition skills across ASD and TDC. Emotional discrimination and person identity perception face processing skills were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 36 publications
5
47
0
1
Order By: Relevance
“…While the two first authors found no group differences in visual attention to faces versus objects [13, 14], Rice et al reported a significantly reduced fixation on faces in ASD compared to controls [15]. …”
Section: Introductionmentioning
confidence: 99%
“…While the two first authors found no group differences in visual attention to faces versus objects [13, 14], Rice et al reported a significantly reduced fixation on faces in ASD compared to controls [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Less attention to the eyes of our face stimuli conceivably could have impaired the ability of participants with ASD to recognize and rate accurately both valence and arousal when viewing emotional faces (Kliemann et al 2010). However, we should also note that a number of studies have shown no significant differences between the eye-gaze behavior of individuals with ASD and healthy controls while viewing emotion faces (e.g., Parish-Morris et al 2013). Without eye-tracking data, we cannot exclude the possibility that subtle group differences in attention to specific facial features influenced our findings.…”
Section: Discussionmentioning
confidence: 79%
“…The following examples represent typical measurement of social attention in the ASD literature: duration of looking to people (face, eyes, mouth) while viewing photographs (Birmingham, Cerf, & Adolphs, 2011; Sasson & Touchstone, 2013), movies (Chawarska, Macari, & Shic, 2012; Parish-Morris et al, 2013), or during live interaction (Freeth, Foulsham, & Kingstone, 2013; Hutman, Chela, Gillespie-Lynch, & Sigman, 2012);orienting (e.g., turning head and/or eyes) to people (Laidlaw, Foulsham, Kuhn, & Kingstone, 2011; Maestro et al, 2002, 2005) or human sounds (Dawson, Toth, et al, 2004); change detection across two nearly identical social scenes (New et al, 2010);gaze following/attention cueing (Greene et al, 2011; Riby, Hancock, Jones, & Hanley, 2013);attention shifting between people and objects (Hutman et al);joint attention behaviors including responding to (e.g., turning eyes and/or head to follow examiner’s point and gaze) and initiating (e.g., gaze, alternating gaze, showing, pointing to share attention) coordinated attention with others (e.g., Barbaro & Dissanayake, 2010; Bedford et al, 2014); smiling and vocalizing while interacting with others (e.g., Maestro et al). The wide variability in conceptualization and measurement of social attention in ASD is clearly apparent in these examples (note that use of the term has been aligned with all three functional categories). In each case, the stated (or implicit) assumption is that various indices of attention to people and/or social communication behaviors (joint attention) operate as a proxy for indexing clinically relevant social attention differences in ASD.…”
Section: Conceptual Approaches To Social Attentionmentioning
confidence: 99%
“…duration of looking to people (face, eyes, mouth) while viewing photographs (Birmingham, Cerf, & Adolphs, 2011; Sasson & Touchstone, 2013), movies (Chawarska, Macari, & Shic, 2012; Parish-Morris et al, 2013), or during live interaction (Freeth, Foulsham, & Kingstone, 2013; Hutman, Chela, Gillespie-Lynch, & Sigman, 2012);…”
Section: Conceptual Approaches To Social Attentionmentioning
confidence: 99%